SAT0148 Short and Long-Term Biological Therapy in Refractory Uveitis of Behcet'S Syndrome. Multicenter Study of 108 Patients. (23rd January 2014) - Calvo-Río, V.; Blanco, R.; Beltrán, E.; S-Bursón, J.; Mesquida, M.; Adán, A.; Hdez-Grafella, M.; Valls, E.; Mtnez-Costa, L.; Sellas, A.; Cordero-Coma, M.; D-Llopis, M.; et al.
Abstract : Objectives: To assess response to biological therapy in uveitis associated to Behçet´s syndrome (BS) refractory to standard immunosuppressants (IS). Methods: Study of 108 patients from 32 hospitals. All of them presented inadequate response to at least 1IS. Inflammation was evaluated according to SUN (Am J Ophthalmol 2005); macular thickness by optical coherence tomography (OCT). Results were expressed as mean±SD, or median [25t-75th(IQR)]. Comparisons were made between baseline and 1 st week, 1 st, 6 th month, 1 st, 2 nd, 3 rd and 4 th year (Wilcoxon). Results: We studied 108 patients/193 affected eyes (59M/49W); mean age 38.2±10.4 years (range 10-67). Before biologic onset they had received iv MethylP (32 cases), CyA (91), MTX (53) or AZA (62). Anti-TNF was 1st choice: infliximab (IFX)(65 cases) and adalimumab (ADA)(43); in monotherapy (22 cases) or in combination: CyA (49 cases), MTX (20), AZA (15), Micophenolate (1), or tacrolimus (1). In refractory or toxicity to 1 st biologic was used; Golimumab (4 cases), Tocilizumab (1), RTX (1) and ETN (1). Anti-TNF follow-up was 35.4±20.2 months. Tyndall, vitritis and OCT showed a rapid and significant improvement at the 1 st week. From biological onset to 2 years of follow-up patients showed an improvement of Tyndall from a median [IQR] of 1 [0-2] to 0 [0-0] (p<0.001), vitritis, 1 [0-2] to 0 [0-0] (p<0.001). At basal, 51 patients, (79 eyes) had macular thickening (OCT>250μ) and 31 (44 eyes) had cystoid macular edema (CME)(OCT>300μ). CME improved from 422.2±118.2 to 280.5±56.4 microns at 2 years (p<0.001). Conclusions: Biological therapy, especially IFX and ADA, yields short and long-term efficacy in uveitis refractory to standard IS in BS. Disclosure of Interest: None Declared